2012
DOI: 10.1037/a0028938
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences moderate the relationship between adolescent language and mentalization.

Abstract: Mentalization refers to the ability to infer mental states of self and others, and this capacity facilitates social interactions. Advances in mentalization theory have proposed that there are both explicit and implicit mentalizing capacities and language may be identified as being an important factor in differentiating these two components of mentalization. Moreover, given apparent sex differences in language and mentalization, we hypothesized that sex may moderate the relationship between language and mentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
(68 reference statements)
2
41
1
Order By: Relevance
“…Taken together, these two studies suggest that AAI RF may be lower among adolescents than adults, a proposition that ought to be explicitly evaluated by examining developmental trajectories of mentalizing. Findings supporting this assertion would fit with the argument that specific brain regions critical for this skill are underdeveloped during adolescence (Fonagy et al, 2002Rutherford et al, 2012). However, adolescents' ability to mentalize may be less developed than adults' when discussing their childhood relationships with their caregivers simply due to the fact that fewer years separate them from their experiences being parented as young children; perhaps the more time lapses, the greater individuals' ability to mentalize regarding prior relationship experiences.…”
Section: Discussionsupporting
confidence: 67%
“…Taken together, these two studies suggest that AAI RF may be lower among adolescents than adults, a proposition that ought to be explicitly evaluated by examining developmental trajectories of mentalizing. Findings supporting this assertion would fit with the argument that specific brain regions critical for this skill are underdeveloped during adolescence (Fonagy et al, 2002Rutherford et al, 2012). However, adolescents' ability to mentalize may be less developed than adults' when discussing their childhood relationships with their caregivers simply due to the fact that fewer years separate them from their experiences being parented as young children; perhaps the more time lapses, the greater individuals' ability to mentalize regarding prior relationship experiences.…”
Section: Discussionsupporting
confidence: 67%
“…RF also was correlated with years of education. Rosenblum et al () found no association between education and reflectivity, Rutherford et al () found that more explicit mentalization was related to better language abilities among adolescent males, and Sadler et al () suggested that RF training was more effective for mothers higher in education. Our significant finding of a relationship between RF and education is in concert with the latter two findings and is unsurprising for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Preschool girls showed more frequent and developmentally more advanced mental-state talk than boys (Hughes & Dunn, 1998), preadolescent girls scored higher than boys on social and self-understanding tasks (Bosacki, 2000), and adolescent girls scored higher than boys on both explicit and implicit mentalization tasks (Rutherford et al, 2012). These gender differences are the result of the interaction of biological, social, and cultural determinants.…”
Section: Rf and Gendermentioning
confidence: 96%